Digital Transformation of Industrial Organizations : Toward an Integrated Framework - Imran, Faisal; Shahzad, Khuram; Butt, Aurangzeab; Kantola, Jussi (Taylor & Francis, 2021)
This article aims to make a difference by exploring industrial digital transformation in order to identify the key enablers and performance outcomes. We highlight the need for alignment and joint optimization of social and technical systems to effectively capitalize on the digital transformation initiatives. Moreover, we call for urgent attention to the development of leaders, as well as the further identification of supportive digital transformation leadership competencies. Competent leaders assume a central role in correcting outdated and invalid assumptions, conceptualizing new ideas, and reinforcing cultural values. Furthermore, we elaborate the necessity of cultural transformation in industrial organizations for impactful digital transformation. Lastly, our findings confirm the significance of organizational structure in digital transformation and simultaneously warn that too little is happening.
Keywords: Digital transformation (DT); industrial organizations; leadership; culture; structure; sociotechnical system theory (STS); fi=Tuotantotalous|en=Industrial Management|